Testing nine critical success factors for tribal self-governance in health care in the United States : a thesis presented in partial fulfilment of the requirements for a Doctor of Philosophy in Public Health at the Research Centre for Māori Health & Development, Massey University, Wellington, New Zealand - Andrews, Mara Kathleen (Massey University, 2025)
This study examines a Critical Success Factor (CSF) Framework for Tribal Self-Governance (TSG) in health care, drawing on the experiences of Native American and Alaska Native Tribes in the United States. The research aims to validate, refine and critique this framework to support Indigenous development, including Tribal Self-Governance and self-determination in Aotearoa/New Zealand. The study employed a mixed-methods approach, comprising documentary analysis, observation, literature review, and expert interviews (n=10). Member-checking interviews with U.S. Tribal Self-Governance practitioners provided additional validation. A deductive analytical framework based on the author’s original CSFs guided the analysis, which broadly followed the U.K. National Centre for Social Research’s Framework Analysis Model. Results confirm the validity of the nine-factor CSF Framework, with refinements to sequence, content and structure. The factors were reorganized into three sets/stages: commitment and initiation, operationalization, and sustainability to suggest a preferred order for those embarking on the Tribal self-governance developmental journey. The research process led to redefining the factors and prioritizing them based on assessment of their relative importance and member feedback. While no major omissions were identified by the research process, a critical analysis of study data provided some cautions and contextual issues for practitioners and governors to be aware of when implementing the framework. The refined CSF Framework aligns favourably with Kaupapa Māori principles, and an implementation plan for the New Zealand context is proposed. This research contributes to our understanding of effective Tribal Self-Governance models and their potential application in diverse Indigenous contexts, including for indigenous Māori in New Zealand.
Keywords: Indigenous, Self-Governance, Sovereignty, Tribes; Māori Doctoral Thesis; 451903 Global Indigenous studies health and wellbeing; 451107 Te kāwana ā-hapori, whakatau take hoki o te Māori (Māori community governance and decision making)